Watermelon juice for lowering blood pressure on hypertensive patients: a case study - Mirqotussyifa Mirqotussyifa (Universitas Pendidikan Indonesia, 2022)
Background: The elderly are susceptible to infectious disease infections due to degenerative problems. Besides that, many non-communicable diseases appear in the elderly, including; diabetes mellitus, arthritis or gout, stroke, and hypertension. Hypertension is a state of increased blood pressure exceeding normal limits, where systolic 140 mmHg and systolic 90 mmHg after two measurements, with an interval of 5 minutes where the patient is calm or at rest. One of the non-pharmacological therapies for hypertension is by consuming watermelon juice. Watermelon is a fruit that contains high enough potassium, water, and fiber, which affects lowering blood pressure. Purposes: This study aimed to determine the effect of giving watermelon juice on reducing high blood pressure. Method: a case study conducted by observation. Results: it was found that after the client consumed watermelon juice for seven days, blood pressure decreased from 180/100 mmHg to 140/80 mmHg. Conclusion: there is an effect on giving watermelon juice to reduce blood pressure in the elderly.